P445 Clinical evaluation of the performance of the most commonly used eumycetoma diagnostic tests using sequencing of the internally transcribed spacer region as the golden standard. (20th September 2022) - Siddig, Emmanuel; Nyuykonge, Bertrand; Mhmoud, Najwa; Abdallah, Omnia; Bahar, Mustafa; Ahmed, Eiman; Nyaoke, Borna; Zijlstra, Eduard; Verbon, Annelies; Bakhiet, Sahar; Fahal, Ahmed; van de Sande, Wendy
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Objective: Mycetoma is a neglected tropical skin disease, caused by 70 different causative agents. For most of the causative agents, molecular identification is the only reliable method to identify the species level. In practice, ultrasound, histopathology, culturing, and species-specific PCRs are most commonly used for species identification. However, the performance of these different tests was not validated using molecular identification by sequencing barcoding genes. Methods: In this study, we validated the performance of the most commonly used diagnostic tools including culture, histopathology, Ultrasound and two species-specific PCR for Madurella mycetomatis on 222 patients suspected of fungal mycetoma by M. mycetomatis ; the sensitivity, specificity, and accuracy of each method was calculated. Results: From the 222 patients, 154 (69.3%) were correctly identified by ultrasound, histology, culture, and both species-specific PCRs. For five patients all tests were negative and for three only the ultrasound was indicative of mycetoma. For the other 60 patients, at least one of the assays was negative for M. mycetomatis . The two species-specific PCRs were the most sensitive and specific, followed by culture and histology. Ultrasound was the least specific as it only allows to differentiate between actinomycetoma and eumycetoma. However, with ultrasound, an identification could be obtained in 9.38 min. PCR took 3.76 h, histology 8.5 days, and culturing 21 days. Conclusion: We concluded that PCR directly on DNA isolated from grains is the most rapid and reliable diagnostic tool to identify M. mycetomatis from eumycetoma grains to use species-specific PCRs. In order to shorten the time to identification of other causative agents, the focus should be on developing more molecular assays for those species.